2010
DOI: 10.1124/jpet.110.174870
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Efficacy of Simvastatin on Prostate Cancer Cells and Tumor Xenografts Is Associated with Inhibition of Akt and Reduced Prostate-Specific Antigen Expression

Abstract: Prostate cancer is the second-leading cause of cancer-associated death among men in the United States. There has been renewed interest in the potential therapeutic benefits of statins for cancer. Simvastatin, a widely used generic drug for preventing cardiovascular events, is well known for its effects on cellular proliferation and inflammation, two key processes that also determine the rate of tumor growth. Although a growing body of evidence suggests that statins have the potential to reduce the risk of many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 39 publications
6
105
0
1
Order By: Relevance
“…In addition, our results showed that simvastatin decreased CCL17-induced HT-29 cell migration without any concomitant effects on cell proliferation of apoptosis, indicating a direct effect of simvastatin on colon cancer cell migration, which might be of beneficial value. Although this is the first report to show that simvastatin inhibits colon cancer cell migration in response to chemokine signaling, other investigations 11 have found that simvastatin can inhibit migration of breast [21], hepatic [22], renal [17] and prostate [23] cancer cells, supporting the concept that simvastatin is an effective inhibitor of tumor cell migration.…”
Section: Role Of Hmg-coa Reductase and Geranygeranylation In Cell Migsupporting
confidence: 58%
“…In addition, our results showed that simvastatin decreased CCL17-induced HT-29 cell migration without any concomitant effects on cell proliferation of apoptosis, indicating a direct effect of simvastatin on colon cancer cell migration, which might be of beneficial value. Although this is the first report to show that simvastatin inhibits colon cancer cell migration in response to chemokine signaling, other investigations 11 have found that simvastatin can inhibit migration of breast [21], hepatic [22], renal [17] and prostate [23] cancer cells, supporting the concept that simvastatin is an effective inhibitor of tumor cell migration.…”
Section: Role Of Hmg-coa Reductase and Geranygeranylation In Cell Migsupporting
confidence: 58%
“…However, several new therapeutic strategies have been recently tested in model organisms [35][36][37][38], including lovastatin [1]. Previously, statins have been reported to decrease proliferation, survival, cell cycle progression, and migration in other cells including aggressive cancer models, amongst others by MAPK pathway inhibition [10,[25][26][27]29,30,[39][40][41]. However, currently evidence that statin treatment will be potent in the most aggressive type of PHEOs/PGLs, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were resuspended in saline to a concentration of 1.7 ϫ 10 7 /ml. Cell suspension (100 l) was injected subcutaneously into 8-week-old nude mice (athymic nude mice; Harlan, Indianapolis, IN) (16). The respective controls were injected intraperitoneally with 0.9% saline.…”
Section: Methodsmentioning
confidence: 99%